2012
DOI: 10.1063/1.4704679
|View full text |Cite
|
Sign up to set email alerts
|

Basal plane dislocation multiplication via the Hopping Frank-Read source mechanism in 4H-SiC

Abstract: Synchrotron white beam x-ray topography (SWBXT) observations are reported of single-ended Frank-Read sources in 4H-SiC. These result from inter-conversion between basal plane dislocations (BPDs) and threading edge dislocations (TEDs) brought about by step interactions on the growth interface resulting in a dislocation comprising several glissile BPD segments on parallel basal planes interconnected by relatively sessile TED segments. Under stress, the BPD segments become pinned by the TED segments producing sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The reduction of the TEDs by 60% is probably due to a conversion into BPDs. The large surface steps deflect some of the TEDs into BPDs, as it was also observed to occur in PVT grown SiC in [13]. Yakimova et al in [14].…”
Section: Discussionmentioning
confidence: 68%
“…The reduction of the TEDs by 60% is probably due to a conversion into BPDs. The large surface steps deflect some of the TEDs into BPDs, as it was also observed to occur in PVT grown SiC in [13]. Yakimova et al in [14].…”
Section: Discussionmentioning
confidence: 68%
“…It also greatly reduced the dislocation density in the copper sheet. Based on Frank-Read (F-R for short) dislocation source mechanism, the proliferation of original dislocations has led to the generation of new dislocations [21]. Therefore, the original dislocation density has a certain effect on the increment of dislocation after surface wear.…”
Section: Effect Of Deformation Rate On Wear Resistance Under Differenmentioning
confidence: 99%
“…On the other hand, the reverse conversion is not energy favored. Wang et al 15 thought this conversion results from the deflection of surface outcrop of a TED onto the basal plane by a macrostep and create a BPD, this is a plausible reason. From our study, the deviation of a BPD line from the basal plane seems to result from the interaction of TED and BPD.…”
Section: Resultsmentioning
confidence: 97%
“…TEM study reveals that complex dislocations consist of BPDs and TEDs connected alternately each other. By using synchrotron white beam X-ray topography, Wang and coworkers 15 found that TED and BPD can convert each other and the BPD multiplies through hopping Frank-Read source with TED serving as pinners in 4H-SiC.…”
Section: Communicationmentioning
confidence: 98%